Changes in legislator vaccine-engagement on Twitter before and after the arrival of the COVID-19 pandemic. Issue 9 (2nd September 2021) - Engel-Rebitzer, Eden; Stokes, Daniel Camargo; Buttenheim, Alison; Purtle, Jonathan; Meisel, Zachary F.
ABSTRACT: Widespread SARS-CoV-2 vaccine uptake will be critical to resolution of the COVID-19 pandemic. Politicians have the potential to impact vaccine sentiment and uptake through vaccine-related communication with the public. We used tweets (n = 6, 201), abstracted from Quorum, a public affairs software platform, to examine changes in the frequency of vaccine-related communication by legislators on the social media platform, Twitter. We found an increase in vaccine-related tweets by legislators following the arrival of SARS-CoV-2 in the United States. In the pre-COVID-19 era the majority of vaccine-related tweets were generated by Democrat and state senators. The increase in tweets following the arrival of COVID-19, however, was greater among Republican and federal legislators than Democrat or state legislators. This suggests that legislators who were previously less engaged in public discussion of vaccination, became engaged following the arrival of SARS-CoV-2, which may have implications for COVID-19 vaccine uptake among their followers.